Parthenogenesis and developmental constraints. Issue 1 (17th October 2019) - Galis, Frietson; van Alphen, Jacques J. M.
Abstract: The absence of a paternal contribution in an unfertilized ovum presents two developmental constraints against the evolution of parthenogenesis. We discuss the constraint caused by the absence of a centrosome and the one caused by the missing set of chromosomes and how they have been broken in specific taxa. They are examples of only a few well‐underpinned examples of developmental constraints acting at macro‐evolutionary scales in animals. Breaking of the constraint of the missing chromosomes is the best understood and generally involves rare occasions of drastic changes of meiosis. These drastic changes can be best explained by having been induced, or at least facilitated, by sudden cytological events (e.g., repeated rounds of hybridization, endosymbiont infections, and contagious infections). Once the genetic and developmental machinery is in place for regular or obligate parthenogenesis, shifts to other types of parthenogenesis can apparently rather easily evolve, for example, from facultative to obligate parthenogenesis, or from pseudoarrhenotoky to haplodiploidy. We argue that the combination of the two developmental constraints forms a near‐absolute barrier against the gradual evolution from sporadic to obligate or regular facultative parthenogenesis, which can probably explain why the occurrence of the highly advantageous mode of regular facultative parthenogenesis is so rare and entirely absent in vertebrates. Abstract : In parthenogenesis an egg cell develops without contribution from a sperm cell. Two crucial missing contributions are the centrosome, necessary for the formation of the spindle in cell divisions and the paternal set of chromosomes, necessary for the restoration of the number of chromosomes. T hese provide two developmental constraints that combine to form a near‐absolute constraint against the gradual evolution from sporadic to regular or obligate parthenogenesis (Boveri, 1887). HIGHLIGHTS: The missing paternal contribution in parthenogenesis presents two hard developmental constraints, one caused by the missing centrosome of the sperm cell and another due to the missing set of paternal chromosomes. We argue that the two developmental constraints combine to provide a near‐absolute constraint against the gradual evolution from sporadic to regular or obligate parthenogenesis The combination of the two developmental constraints can probably explain why the occurrence of the highly advantageous mode of regular facultative parthenogenesis is so rare and entirely absent in vertebrates